Numerical Investigation on Charging–Discharging of a PCM Using PV and Thermal Oil for Injera Baking Application - Meseret Alemu Abinet; Abdulkadir A. Hassen; G. Gashaw (International Journal of Photoenergy)
In Ethiopia, where millions rely on biomass, charcoal, and animal dung for energy, the predominant use is in baking injera, constituting over 50% of energy consumption. This traditional practice adversely affects the health of women and children and hampers education. To address this, solar energy is explored as a sustainable alternative. However, the intermittent nature of solar power poses challenges. A solution involves integrating a thermal storage system, ensuring a consistent and reliable energy supply for the crucial task of baking injera, ultimately improving lives and empowering communities. This study investigates the thermal characteristics of the charging and discharge processes and main heat transfer processes in the injera baking system with PV which was integrated with the thermal storage system. Our study journey began with exploring relevant papers and system designs, collecting and analyzing data, and, in addition, performing mathematical and numerical models. A numerical simulation was conducted using a finite-difference computational model for the thermal storage containing PCM and thermal oil. The thermal oil was used to store energy and transfer heat; furthermore, the developed computational models were analyzed using MATLAB programming software. The numerical simulation result by using solar radiation data from Addis Ababa showed that the thermal storage has the capacity to store about 33.03 MJ during charging using constant heat flux which was from the PV. The amount of energy discharged from the PCM was 13.1 MJ, and from the thermia oil, it was 3.50 MJ using natural convection heat transfer, and the discharging and overall efficiency of the system were about 50.2% and 46.67%, respectively. Also, the baking pan surface temperature stayed between 220°C and 146.4°C for about 3 h. This result was compared with different papers, and it can be concluded that the numerically investigated solar-powered injera baking integrated with thermal storage showed a promising result.